Reliability analysis of irregular zones in pipelines under both effects of corrosion and residual stress. (April 2019) - Nahal, M.; Chateauneuf, A.; Sahraoui, Y.
Abstract: In this work, both effects of corrosion and residual stress on the irregular zones of a pipeline is investigated. A finite element model of a corroded elbow area, butt welding area and flange area is proposed, coupled with usual residual stress models. The probabilistic is then developed to provide a realistic corrosion parameters and time modeling, leading to the real impact on the lifetime of a burred pipeline. The failure probability and reliability index of various corroded areas are computed by using Monte Carlo simulations. A numerical case study with three different corrosion rates (low, moderate and high corrosion rate) allows us to estimate the impact of various factors on the reliability of the corroded pipes. The obtaining result shows that it is necessary to ensure the inspection of the irregular areas in pipelines in order to better manage their lifetimes. Highlights: A numerical corrosion model was developed using finite element method. An empirical mechanical behavior model of a three corroded irregular zones in pipeline is proposed. A probabilistic model was also developed and coupling with the mechanical proposed models. A methodology for estimating time-dependent reliability of a corroding pipeline over its lifetime is developed. The effect of a high, moderate and low corrosion rates have been studied.